Pengaruh Jenis Kelamin dan Umur Terhadap Karkas dan Sisa Karkas Kerbau Lumpur di Rumah Potong Hewan Banda Aceh - Mawardi Mohd. Ali (Agricultural Faculty, 2000)
ABSTRACT.The effect of sex and old to carcass and offal of swamp Bufallo at Rumah Potong Hewan Banda Aceh, have been done in Banda Aceh as long as 10 days. The material that was used were swamp bufalloes from Banda Aceh regency, as much as 36 bufalloes, that was sparated 18 females and 19 males. The aim of this study was to know the partial and interaction effect of sex and old to carcass percentage and offal of swamp bufalloes. The method used of this study was direct observation at Rumah Potong Hewan. The variable that was knowed were; the heavy of: weight, carcass, head, hide, heart, feet, liver, lungs, spleen, full digestive tract, and the carcass percentage. The data collected was Analyzed by completely Randomized Design (CRD), wich 3x2 factorial pattern and six times replication. As a main factor was old, that was sparated by 3 4 years, 4 5 years, and 5 years. The data was tested by Duncans test. The result of this study showed that was not any interaction effect of old and sex to carcass percentage and offal. Also, that not any effect of sex to carcass percentage, but effect of sex was significance different to offal. The other hand, not any effect of old to carcass percentage and offal.